Muscle Quality and Proteolytic Enzymes of Farmed Atlantic Cod (Gadus morhua) During Storage: Effects of Pre-Slaughter Handling and Increased Storage Temperature. Issue 4 (18th May 2016) - Hultmann, Lisbeth; Tobiassen, Torbjørn; Aas-Hansen, Øyvind; Phu, Tran Minh; Rustad, Turid
ABSTRACT: In the present experiment, the characteristics of minimally handled, directly slaughtered farmed Atlantic cod were compared to cod subjected to 2 h preslaughter handling stress. The results strongly indicate that increasing the storage temperature from 0 to 5°C had a larger negative impact on the quality characteristics than the handling stress applied. Further, there may be interaction effects between handling, storage temperature, and storage time.